Biopsychosocial factors associated with non-recovery after a minor transport-related injury: protocol for a systematic review. Issue 9 (3rd September 2017) - Samoborec, Stella; Ruseckaite, Rasa; Romero, Lorena; Evans, Sue M
Abstract : Introduction: Globally, road transport accidents contribute substantially to the number of deaths and also to the burden of disability. Up to 50 million people suffer a transport-related non-fatal injury each year, which often leads to long-term disability. It has been shown that substantial number of people with minor injuries struggle to recover and the reasons are still not well explored. Despite the high prevalence, little is known about the factors hindering recovery following minor traffic-related injuries. The aim of this paper is to present a protocol for the systematic review aiming to understand biopsychosocial factors related to non-recovery and identify current gaps in the literature. Methods and analysis: The review will be conducted in compliance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocol guidelines. A search of the electronic databases, MEDLINE, EMBASE, Cochrane Central Register of Controlled trials, will be undertaken, in addition to Google Scholar and grey literature to identify studies in period from 2006 to 2016. Quantitative and qualitative research articles describing and identifying biopsychosocial factors associated with non-recovery and health outcomes such as pain, disability, functional recovery, health-related quality of life, post-traumatic stress disorder, depression, anxiety and return to work will be included. A conceptual framework developed to identify biopsychosocial factors will be applied to assure defined criterion. At present, there is little anticipation for meta-analyses due to the heterogeneity of factors and outcomes assessed. Therefore, a narrative synthesis based on study findings will be conducted. Ethics and dissemination: Ethical approval is not required as primary data will not be collected. Review results will be published as a part of thesis, peer-reviewed journal and conferences. Trialregistration number: PROSPEROregistration number: CRD42016052276.